公教分途的實然與應然-以公立大學兼任行政職務教師校外兼職管理規範為焦點之問題建構 Differentiating Teachers from Government Employees: Regulations on Teachers With Concurrent Administrative Positions at National Universities - 紀茂嬌 Mao-Chiao Chi; 賴怡樺 Yi-Hua Lai; 連雅慧 Bella Ya-Hui Lien (National Taiwan Normal University, 2022)
現行公立大學教師之人事管理自1992年大法官會議釋字第308號解釋始明確界定公教分途原則，即公立學校教師不屬於《公務員服務法》所稱之公務員，惟兼任學校行政職務之教師，就其兼任之行政職務，則有《公務員服務法》之適用。然而本質上，教研工作較強調興利、創意與彈性，行政公務則較著重防弊、控管與安全，過度管制可能影響高等教育的全球競爭力，也可能影響教師兼任行政職務的意願。本研究聚焦於針對公立大學兼任行政職務教師的「校外兼職管理」進行評估。透過立意抽樣16所大學人事室實施半結構式問卷調查、深度訪談10位大學校長與一級主管，以分析兼任行政職務教師校外兼職問題評估，並分別透過批判系統啟發法的三個面向：範圍評斷、應然面與實然面加以分析，呈現有關問題與論辯。 本研究發現兼任行政職務教師較常出現爭議的兼職類型為「營利事業機構或團體」與「非營利事業機構或團體」，為提升國際化及競爭力，大學教師應藉專業和產業連結，善盡社會責任與貢獻國家。因此建議校外兼職應逐步授權學校建立規範與管理，且根據行政職務與兼職行為之相關性，亦應研議適度放寬管理規範。 At present, human resource management of public university teachers in Taiwan is mainly based on the University Act, the Teachers' Act, and the Act of Governing the Appointment of Educators. Since 1992, interpretation No. 308 of the Grand Justices Council has clearly defined the "distinction between teachers and government employees," that is, teachers who also work as administrators fall under the jurisdiction of the Civil Servant Work Act. However, teaching and research emphasize profitability, creativity, and flexibility, whereas administrative duties center on prevention, control, and safety. Overregulation of the legal system may affect the competitiveness of universities and the willingness of teachers to assume administrative positions. Furthermore, with regard to the concurrent administrative positions of teachers, one should question whether (1) the rights and obligations of teachers should differ from those of government employees, (2) whether these differences would be appropriate and fair, (3) whether the regulations would be uniformly applied, (4) whether standardization of practice should be applied, and (5) whether the public is concerned with any relevant issues. Unfortunately, related studies differentiating teachers and government employees have adopted a normative focus. This paper intends to further explore the diagnosis and evaluation of these practical problems mentioned above. To strengthen the development of science and technology in the country and promote cooperation between industry and academia, most studies have advocated for relaxing regulations to encourage university teachers to engage in off-campus part-time activities. Some mechanisms, such as the conflict-of-interest avoidance regulations and disclosure, achieve this without being restricted by the Act of Governing the Appointment of Educators and the Civil Servant Work Act. However, a review of existing laws and regulations that govern the rights and obligations of teachers who hold administrative positions under civil service regulations showed that these laws and regulations are strict for teachers who do not also hold administrative positions. If schools establish internal control mechanisms of self-regulation, further planning and consensus building on the specific regulations are required. This study assessed the regulations on off-campus part-time activities undertaken by teachers who hold a concurrent administrative position at a national university. Moreover, this study explored various perspectives to determine the necessity of adjusting legal regulations. Therefore, the critical systems heuristics model was adopted as the analytical framework. This study evaluated the management of off-campus part-time activities by teachers who hold a concurrent administrative position at a national university. Through sampling 16 university personnel office documents and interviewing 10 university presidents and first-level executives, this study analyzed the off-campus part-time activities by teachers holding a concurrent administrative position. The analysis focused on three aspects of the critical system-inspired approach: position judgements, value evaluation, and observation. The results of the survey indicated that teachers often hold an administrative position at a national university to engage in activities on the side. The percentage of comprehensive and technology-based universities where teachers worked at was significantly higher than that of professional schools. The most controversial among these part-time activities which teachers involved is working at for-profit and non-profit organizations and groups. The interviews indicated that the respondents had diverse opinions about the regulations of off-campus part-time activities. The three main positions expressed by the participants were (1) the regulations should be the same as those for government employees, (2) the regulations should be the same as those for non-administrative teachers, and (3) the regulations should depend on the nature of the administrative matters which teachers are in charge. Among them, position 1 had fewer supporters compared with positions 2 and 3.In conclusion, universities rely on teachers to become more global and competitive. Teachers do so by linking their theoretical and practical expertise, fulfilling their social responsibilities, and contributing to society. If teachers are restricted from having a part-time position because of their concurrent administrative position, it may decrease their intention to involve in administrative positions thus hinder the recruitment of exceptional administrative professionals and the development of the university. This paper proposes two recommendations for policy makers: (1) off-campus part-time activities should be gradually authorized in regulations and administration, and (2) the university should appropriately relax regulations based on the relationship between administrative duties and part-time activities.